If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + -6t = 1 + 2 Combine like terms: 3t + -6t = -3t -3t = 1 + 2 Combine like terms: 1 + 2 = 3 -3t = 3 Solving -3t = 3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Divide each side by '-3'. t = -1 Simplifying t = -1
| (3x+5)-(x+5)=24 | | 3t-6=1+2 | | 3+-6=1+2 | | -4y^2-20y+5=0 | | 7x-9x+6=x-2+8 | | (5x+y+4)(5x+y+4)=0 | | X^2+16-57= | | -(5x-3y+1)= | | -2x^2-x=-9x+8 | | 2x-2=.25x+6 | | (8x+7y-5)(8x+7y+5)=0 | | 8x-16=200 | | 4(2-11)-6x=-3 | | 0.12-0.01(x+3)=-0.01(1-x) | | 5(y-1)=y+9-2(-6y-2) | | 7x=171 | | 525-6x=339 | | 0.04x=0.16 | | T=t+s+r | | 8x+5y=-9 | | 3(x+7)=-3(4x-9)+5x | | 3x-3x+2=7 | | -4y+2y=-15 | | (5a+6)(5a^2+4a+6)=0 | | 2b+4=2 | | -225x-4950=225x+50 | | 40-3.1415x=0 | | 40-pix=0 | | 5u-7+2(2u+5)=-3(u+5) | | 7(5c+9)=-24+8c | | 2(y-8)=6y-20 | | 2x-1=.25x+6 |